Seasonal variability of the North Equatorial Current–Kuroshio Current–Mindanao Current based on observations - Wang, Fujun; Zhang, Linlin; Feng, Junqiao; Hu, Dunxin (Frontiers in Marine Science, 2022)
Utilizing the direct mooring observation along 130°E (10.5°N, 13°N, 15.5°N, and 18°N), 18°N (122.7°E, 123°E, and 123.3°E), and 8°N (127°E) and satellite data, the seasonal variabilities of the North Equatorial Current (NEC), Kuroshio Current (KC), and Mindanao Current (MC) were investigated. The southern part of the NEC along 130°E, the KC along 18°N, and the MC along 8°N featured similar seasonal cycles: that is, the currents were strong in spring and weak in autumn, while the KC along 18°N featured another peak in winter. Moreover, the seasonal phase of the NEC along 130°E was latitude-dependent; it advanced slightly from 10°N to 14°N and delayed poleward. The seasonal variabilities of the three currents were mainly controlled by local winds and Rossby waves via a geostrophic relationship, as the mooring observation was consistent with satellite data. The calculation shows that the local wind was dominant in the above mentioned in-phase areas (i.e., the southern part of the NEC, KC, and MC), while Rossby waves played an important role in the northern part of the NEC. The results indicate that the NEC–KC–MC system had the same zonal dynamics but different meridional dynamics across seasons.